Bilateral and unilateral asymmetries of isokinetic strength and flexibility in male young professional soccer players - Daneshjoo, A.; Rahnama, N.; Mokhtar, A. H.; Yusof, A. (Journal of Human Kinetics, 2013)
This study investigated bilateral and unilateral asymmetries of strength and flexibility in male young professional soccer players. Thirty-six soccer players (age: 18.9 ± 1.4 years) participated in this study. A Biodex Isokinetic Dynamometer was used to assess the hamstring and quadriceps strength at selected speeds of 60°/s, 180°/s and 300°/s. Hip joint flexibility was measured using a goniometer. No difference was observed in conventional strength ratio, dynamic control ratio and fast/slow speed ratio between the dominant and non-dominant legs (p>0.05). All but one of the players (97.2%) had musculoskeletal abnormality (bilateral imbalance > 10%) in one or more specific muscle groups. The dominant leg had greater hip joint flexibility compared with the non-dominant leg (108.8 ± 10.7° versus 104.6 ± 9.8°, respectively). The findings support the hypothesis that physical performance and movement pattern experienced during soccer playing may negatively change the balance of strength in both legs (bilateral strength balance), but not on the same leg of the young male professional soccer players. The results can be helpful for trainers and coaches to decide whether the players need to improve their balance and strength which in turn may prevent injury. It is suggested that in professional soccer training, quadriceps and hamstrings muscle strength, as well as hip joint flexibility should not be overlooked.